Clinical and Pathological Findings of a Fatal Systemic Capillary Leak Syndrome (Clarkson Disease): A Case Report. Issue 9 (March 2015) - Zancanaro, Andrea; Serafini, Francesco; Fantin, Giuseppe; Murer, Bruno; Cicardi, Marco; Bonanni, Luca; Vestra, Michele Dalla; Scanferlato, Mauro; Mazzanti, Giovanni; Presotto, Fabio
Abstract : Abstract: Systemic capillary leak syndrome (SCLS) is a rare disorder with episodes of hypotension, hypoalbuminemia, and hemoconcentration. During attacks endothelial hyperpermeability results in leakage of plasma proteins into the interstitial space. Attacks vary in severity and may be lethal. A 49-year-old previously healthy man was admitted to hospital for hypovolemic shock, anasarca with pleuropericardial effusion, muscle fatigue, and oliguria occurring after a flu-like syndrome. Laboratory data showed an increase in hematocrit (65%), leucocytes (24.590 μ/L), creatinine (2.5 mg/dL), creatine phosphokinase (10.000 U/L), and a decrease in serum albumin (17 g/L) without proteinuria. Immunoglobulins of class G/λ monoclonal gammopathy were detected (1.3 g/L). The initial suspicions addressed to a protein-loosing syndrome or to an effort-related rhabdomyolysis. Initial therapy was based on steroids, albumin, and high molecular weight plasma expanders (hydroxyethyl starch). Because of high hematocrit, phlebotomy was also performed. The patient had complete clinical remission and a diagnosis of SCLS was finally made. He received prophylactic therapy with verapamil and theophylline that was self-stopped for intolerance (hypotension and tachycardia). He had a new crisis 2 days after a physical effort, and was admitted in intensive care unit. The patient died for severe hypovolemic shock with multiorgan failure and sudden cardiac arrest 15 hours after hospital admission. Postmortem investigation revealed massive interstitial edema of main organs with myocardial hyperacute ischemia. Studies on SCLS are limited for the rarity of the disease and its unpredictable course. Both prophylactic and acute crisis treatments are empirical and optimal management of severe attacks is still lacking.